Remote Sensing for Irrigation Water Management—The State of the Art and Prospects for Near‐Future Operations - Wim G. M. Bastiaanssen; Chris Perry; Royce Dalby; Yasir Mohamed; Xueliang Cai; Poolad Karimi; IJsbrand de Jong; Pasquale Steduto; Marat Beksultanov; Christopher C. M. Neale; David Molden; Waqas Awan; et al. (Irrigation and Drainage, 2026)
A recent UN report describes many regions as facing ‘water bankruptcy, ’ a condition in which available water resources can no longer meet existing demands. In practice, this means irrigation will likely bear the greatest burden of future water‐use reductions, a complicated and fraught decision to make given its critical role in food security. This review paper highlights the growing range of information now available through remote sensing technologies to support planners, irrigation managers and farmers. These data include cropping patterns, crop yields, water consumption, farmgate water and tubewell water deliveries, soil moisture and root‐zone water storage, among others. The paper also reviews current applications of remote sensing, which remain too often constrained to the scientific community, and recommends the development and dissemination of standardized irrigation analytics and diagnostic tools. Government irrigation and water agencies are encouraged to integrate these emerging spatial data sources into both strategic planning and real‐time management from field to scheme scale and provide a stronger foundation of key performance indicator (KPI). Bridging this information gap will require startups and technology providers to translate advanced data products into practical, user‐friendly tools tailored to the needs of the irrigation sector.

Reproductive interference between honeybee species in artificial sympatry - Emily J. Remnant; Anna Koetz; Ken Tan; Eloise Hinson; Madeleine Beekman; Benjamin P. Oldroyd (Molecular Ecology, 2014)
Reproductive isolation between closely related species is often incomplete. The Western honeybee, A pis mellifera , and the E astern hive bee, A pis cerana , have been allopatric for millions of years, but are nonetheless similar in morphology and behaviour. During the last century, the two species were brought into contact anthropogenically, providing potential opportunities for interspecific matings. Hybrids between A. mellifera and A. cerana are inviable, so natural interspecific matings are of concern because they may reduce the viability of A. cerana and A. mellifera populations – two of the world's most important pollinators. We examined the mating behaviour of A. mellifera and A. cerana queens and drones from Caoba Basin, China and Cairns, Australia. Drone mating flight times overlap in both areas. Analysis of the spermathecal contents of queens with species‐specific genetic markers indicated that in Caoba Basin, 14% of A. mellifera queens mated with at least one A. cerana male, but we detected no A. cerana queens that had mated with A. mellifera males. Similarly, in Cairns, no A. cerana queens carried A. mellifera sperm , but one‐third of A. mellifera queens had mated with at least one A. cerana male. No hybrid embryos were detected in eggs laid by interspecifically mated A. mellifera queens in either location. However, A. mellifera queens artificially inseminated with A. cerana sperm produced inviable hybrid eggs or unfertilized drones. This suggests that reproductive interference will impact the viability of honeybee populations wherever A. cerana and A. mellifera are in contact.